PENGARUH EFEKTIVITAS STRATEGI PELAYANAN DINAS KEBUDAYAAN DAN PARIWISATA KOTA PARIAMAN TERHADAP KEPUASAN PENGUNJUNG PANTAI GANDORIAH - Mesa Widya Maharani; Aldri Frinaldi; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aimed to determine the effect of the effectiveness of the Pariaman City Culture and Tourism Service strategy on visitor satisfaction at Gandoriah Beach. The background of this research is due to the finding of problems on the effectiveness of service strategies that are not good for visitor satisfaction at Gandoriah Beach. This type of research is quantitative research. The population of this study were visitors who traveled to Gandoriah Beach. Sampling is by using the Slovin formula and the sampling technique in this study is Simple Random Sampling. The sample in this study totaled 255 people. Data collection in this study uses a questionnaire with a Likert scale measurement scale. Furthermore, the classical assumption test consists of normality test, linearity test, heteroscedasticity test, multicoloniality test and autocorrelation test. After that, a simple linear regression test, a research hypothesis test. The results showed that there was a significant influence on the effectiveness of the Pariaman City Tourism and Tourism Office strategy on visitor satisfaction at Gandoriah Beach. Strategic effectiveness variables contribute to visitor satisfaction by 14% while the remaining 86% is influenced by other variables not examined in this study.